Perancangan Sistem Absensi Peserta Didik Berbasis Website di SMA Negeri 1 Ambarawa - Satria Adi Negara, Satria Adi Negara; Tambotoh, Johan; Tanaamah, Andeka Rocky (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The manual attendance system running at SMA Negeri 1 Ambarawa currently uses written attendance by recording students' attendance every hour in a class journal. This system requires quite a long time to collect attendance data; the possibility of errors in data recording by officers is also quite large because the recording is done manually. The research method used is Design Science Research (DSR). The DSR method is a methodology used for research in the field of information technology. This method is oriented towards system information design. The results of this research produce an information system application that can optimize the management of student attendance data. Storing attendance data digitally can be an alternative for teachers managing student attendance data, making it easier for students to access the files when needed. Apart from that, this system can make it easier for teachers to input and recapitulate student attendance to control student attendance discipline as a form of accountability to parents.